Typology of the Mentality of Rural Women About Promotion of Rural Entrepreneurship - Mohammad Bagher Arayesh (Pizhūhish/hā-yi Rūstāyī, 2019)
The present research was conducted on the typology of mental models of rural women for rural entrepreneurship development in Ilam province. The study deals with the subjective opinions of the participants based on Q methodology. It is applied in terms of goal as well as exploratory and mixed in terms of data collection. The participants of the study consisted of 26 successful female rural entrepreneurs selected by the targeted judgment method. The data were obtained through interviews and a literature review. As many as 49 phrases were selected as Q statements. The SPSS software was applied for data analysis. According to the results obtained from the exploratory factor analysis, the mentality of the participating rural women about promoting rural entrepreneurship was classified into six types including entrepreneurial, market-driven educational, economy-centered, environment-centered,  participatory, and supportive types.